Ustadz Abdul Somad and the Future of Online Da’wa in Indonesia - Ridho, Miftahur (Universitas Islam Negeri Sultan Aji Muhammad Idris Samarinda, 2019)
Rapid developments in the area of information technology have transformed the nature of social interactions among people in the world. Da’wa, as a form of social interaction aimed at conveying the teachings of Islam towards all people in the world, changes as the platform of undertaking the Da’wa itself, the available media of interactions, change. The aim of this paper is to analyze the strategy of Ustadz Abdul Somad (UAS), the currently most popular preacher in Indonesia, in utilizing the internet for the purpose of Da’wa (Islamic propagation). Findings reveal that UAS’s success lies on his ability to persuade his audience to record his sermons and post them individually to the internet, especially on video-sharing platform of youTube.com. Abdul Somad even claimed himself as a preacher of million viewers. However, his sermons are mostly uploaded to the internet by his audiences. Abdul Somad does not rely on professional team to craft his sermons and post them online. This strategy of allowing his audience to create and share user generated contents is proven to highly successful. Not only that Abdul Somad is able to secure millions of viewers online, it also helps him to multiply the proliferation of his sermons with relatively no cost.